PERSEPSI AKAN GAJI, MOTIVASI KERJA, DAN KINERJA KARYAWAN PT. AMITA BARA SEJAHTERA - Eddy Madiono Sutanto; Ferdian Mario Patty (STIE Perbanas Surabaya, 2014)
Employee performance is a process which is used by an organization to evaluate and judge the work performance of the employees. There are two variables that have been used to review the performance of employee in PT. Amita Bara Sejahtera, which are salary and work motivation. This research goal is to observe the influences of salary and work motivation effect partially and simultaneously towards work performance, to observe the dominant variable between salary and work motivation towards performance, and observing another factor that influence the work performance of the employees in PT. Amita Bara Sejahtera. Data collecting used questionnaire with judgment sampling to 50 employees with some criteria. The result of analysis using multiple linier regression is that salary and work motivation are positively influenced the performance of employee in both partially and simultaneously.